Extreme wind‐ice interaction over Recovery Ice Stream, East Antarctica. Issue 19 (12th October 2015) - Das, Indrani; Scambos, Ted A.; Koenig, Lora S.; van den Broeke, Michiel R.; Lenaerts, Jan T. M.
Abstract Surface snow accumulation over East Antarctica is an important climate indicator but a difficult parameter to constrain. Surface mass ablation dominates over persistent wind‐scour zones as near‐surface katabatic winds accelerate over locally steeper ice surface topography, and sublimate and redistribute snow. Here we quantify ablation rates and downwind redeposition of snow over wind‐scour zones in the upper Recovery Ice Stream catchment. Airborne radio echo‐soundings show a gradual ablation of ~16–18 m of firn, corresponding to ~200 years of accumulation, over these zones and ablation rates of ~54 kg m−2 a−1 (54 mm water equivalent a−1). We conclude that mass loss is dominated by sublimation and mass is transported downwind as water vapor, because snow redeposition downslope of the wind‐scour zones constitutes only a small fraction (<10%) of the cumulative mass loss.